2014 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2014
DOI: 10.1109/bibm.2014.6999249
|View full text |Cite
|
Sign up to set email alerts
|

Using independent component analysis to obtain feature space for reliable ECG Arrhythmia classification

Abstract: Electrocardiogram (ECG) reflects the activities of the human heart and reveals hidden information on its structure and behaviour. The information is extracted to gain insights that assist explanation and identification of diverse pathological conditions. This was traditionally done by an expert through visual inspection of ECGs. The complexity and tediousness of this onus hinder long-term monitoring and rapid diagnosis, computerised and automated ECG signal processing are therefore sought after. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Aiming at reducing the dimension of the feature vector, various techniques have been applied directly on the samples that represent the heartbeat (in the neighborhood of the R peak) as principal component analysis (PCA) [75,76,77], or independent component analysis (ICA) [78,79,80], in which new coefficients are extracted to represent the heartbeat. Chawla [81] presents a comparative study between the use of PCA and ICA to reduce the noise and artifacts of the ECG signal and showed that PCA is a better technique to reduce noise, while ICA is better one to extract features.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Aiming at reducing the dimension of the feature vector, various techniques have been applied directly on the samples that represent the heartbeat (in the neighborhood of the R peak) as principal component analysis (PCA) [75,76,77], or independent component analysis (ICA) [78,79,80], in which new coefficients are extracted to represent the heartbeat. Chawla [81] presents a comparative study between the use of PCA and ICA to reduce the noise and artifacts of the ECG signal and showed that PCA is a better technique to reduce noise, while ICA is better one to extract features.…”
Section: Feature Extractionmentioning
confidence: 99%
“…In terms of accuracy, refs. [46] and [47] have the closest but still a lower accuracy than our proposed algorithm, i.e., 99.61% and 99.80%, respectively. Note that, ref.…”
Section: On the Effect Of Depthwise Separable Cnnmentioning
confidence: 85%
“…Note that, ref. [46] only performs classification for eight classes, while [47] only performs classification for four classes, while we perform classification for sixteen classes. Hence, it is evident that our proposed algorithm with the [256 256 256] ensemble of CNNs outperforms the other algorithms.…”
Section: On the Effect Of Depthwise Separable Cnnmentioning
confidence: 99%
“…Using large feature vector can make slow classification algorithm. The dimension of feature vector can be reduced using various techniques like principle component analysis (PCA) [40], [41], [42] or Independent component analysis (ICA) [43],[39], [25]. Some other different techniques are also introduced by authors, like Hermite transform [44], clustering [45], [46], [47], random projection [48], Lyapunov exponent [49], [50], projected and dynamic [38].…”
Section: Feature Extractionmentioning
confidence: 99%